A Tale of Agony of Spiny-Tailed Lizard: Conservation, Poaching and Trade Dynamics in Western Rajasthan, India - Chauhan, Vivan; Rawat, Mamta; Badola, Saket; Dookia, Sumit (Indian Forester, 2024)
The Indian spiny-tailed lizard, Saara hardwickii (Gray, 1827) is a key stone species of the desert ecosystem, many raptors and meso-carnivores like foxes and small cats feed on these lizards. A study to understand the level of poaching, its hot spots and ultimately to find out the trade route from study area to the rest of country, was conducted between January to June 2019. Field surveys, semi-structured interviews of locals, few former poachers and expert interviews were conducted to understand its current population distribution, poaching hot spots and probable trade route from Rajasthan to the rest of country. It was found that despite stringent laws poaching is still rampant for meat as well as extraction of oil from its reserve fat glands. This oil is believed to be aphrodisiac in nature and is major cause of its population decline. Recently this species has been upgraded from Schedule II (Part I) of Wildlife (Protection) Act, 1972 to Schedule I; as well as also from Data Deficient to Vulnerable in Red List of IUCN. Such level of changes in the protection status to this species will surely prove a millstone in its conservation efforts.